The life-cycle and ultrastructure of Sarcocystis ameivamastigodryasi n. sp., in the lizard Ameiva ameiva (Teiidae) and the snake Mastigodryas bifossatus (Colubridae) - Lainson, Ralph (EDP Open, 2021)
Sarcocysts in muscles of the teiid lizard Ameiva ameiva from north Brazil were fed to the colubrid snake Mastigodryas bifossatus, the faeces of which had been shown to be devoid of coccidial oocysts or sporocysts. When necropsied 16 days later the snake was shown to have developed a massive intestinal infection of Sarcocystis. Mature sporocysts from another, naturally infected M. bifossatus were fed to juvenile specimens of A. ameiva in which no sarcocysts could be detected in tail muscle biopsies. When examined 30 and 47 days later they had very large numbers of sarcocysts in their tail and tongue muscles. The parasite is given the name of Sarcocystis ameivamastigodryasi n. sp. An ultrastructural study has been made of the sarcocyst and of the parasite's sporulation in the lamina propria of the snake: the latter provides details of the wall formation process in developing sporocysts. Attempts to infect a specimen of the boid Boa constrictor constrictor by feeding it with infected Ameiva failed, suggesting that sporocysts previously recorded in genera of the family Boidae may be those of a different species of Sarcocystis.